Extraneural metastasizing ependymoma of the spinal cord - Graf, Matthias; Bläker, Hendrik; Otto, Herwart F. (Pathology & oncology research, 1999)
This paper reports a case of the rare entity of an extraneural metastasizing ependymoma of the spinal cord. The tumor which arose in the conus medullaris and in the cauda equina was first diagnosed in 1956 when a thoracolumbar myeloresection was performed. At autopsy, 40 years after the primary diagnosis, a massive local tumor recurrence with extraneural metastases in the lungs, the pleura, the liver, and the thoracal and abdominal lymph nodes were found. Immunohistochemical stains of the extraneural metastases showed a strong cytoplasmatic expression of glial fibrillary acidic protein (GFAP). Neither the primary tumor nor its metastases showed any of the conventional morphological criteria of malignancy. Reviewing the literature we discuss the possible mechanism of extraneural tumor spread and the incidence of metastases with regard to the tumor type.